River Basin Surveys Papers, No. 2: Prehistory and the Missouri Valley Development Program Summary Report on the Missouri River Basin Archeological Survey in 1949 - Wedel, Waldo R.; Smithsonian Institution; Bureau of American Ethnology (UND Scholarly Commons, 1953)
Published as a series sponsored by the Smithsonian Institution Bureau of American Ethnology, the “River Basin Surveys Papers” are a collection of archeological investigations focused on areas now flooded by the completion of various dam projects in the United States. The River Basin Surveys Papers (numbered 1-39) were mostly published in bundles with 5-6 papers in each bundle. In collaboration with the United States (US) National Park Service and the US Bureau of Reclamation, the US Department of the Interior, and the US Army Corps of Engineers, the Smithsonian Institution pulled archeological and paleontological remains from several sites prior to losing access to the sites due to flooding. The Smithsonian Institution calls this project the Inter-Agency Archeological Salvage Program. Paper number 2 provides a summary of the progress made on the River Basin Surveys project for the 1949 calendar year. The summary is divided into four sections: personnel, laboratory activities, fieldwork and explorations, fieldwork by cooperating agencies. The sections are, when applicable, broken down by state, citing work in Nebraska, North Dakota, South Dakota, Wyoming, and Kansas. The author notes that 1949 was a difficult year for the project. This paper includes photographs. https://commons.und.edu/indigenous-gov-docs/1133/thumbnail.jpg